Narrativa critico reflexiva sobre o curso de medicina da Universidade Federal de São Carlos: visões e opiniões sobre a metodologia construtivista empregada no curso de medicina da UFSCar na formação do profissional - Barros, Jean Carlos de Souza (Universidade Federal de São Carlos, 2023)
Introduction: This work is built on an autobiographical and critical-reflexive narrative about the medical course at the Federal University of São Carlos, presenting the facilities and difficulties of self-directed learning proposed by the faculty, its importance as a methodology and its failures according to the author's opinion according to lived realities. Objective: Expose facts and opinions about the constructivist method and its application in the medical course at UFSCar, generate reflections on how it is put into practice and how the student figure receives it. Method: The methodology used for this course completion work consists of author reports and literature reviews with consultation of electronic materials found in SCiELO about the constructivist methodology. Conclusions: It is possible to conclude that there was an important effort by the medical course at the Federal University of São Carlos to remain faithful to the constructivist method based on problems. However, not everyone, as much as they wanted the method, fully adapted to the method, culminating in insecurities, fears and anxieties due to the lack of traditional assessment methods or the early introduction of the student to health services, even if unprepared.
Critical reflective narrative about the medical course at the Federal University of São Carlos: views and opinions on the constructivist methodology used in the medical course at UFSCar in professional training
Keywords: Educação Médica; Espiral construtivista; Metodologia construtivista; Aprendizado baseado em problema; PBL; Medical education; Constructivist spiral; Constructivist methodology; Problem based learning; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM